The Subtitling Strategies Of “Gift” From English Into Indonesian Applied in The Subtitle Of Movie “Encanto” - Putu Giorgiana Ananta Suyasa; I Komang Sumaryana Putra; Ni Luh Sutjiati Beratha (Pusat riset dan Inovasi Nasional, 2025)
This study is entitled The Translation Strategies Of “Gift” From English Into Indonesian Applied In The Subtitle Of The Movie Encanto. This study aims to find out the subtitling strategies applied in translating the Indonesian subtitle of an English movie Encanto and analyze the translation equivalence of the movie subtitle. The data were taken from the Indonesian subtitle of Encanto movie using the streaming movie platform Disney+ Hotstar. The data were collected using the documentation method with a note-taking technique. Descriptive methods with qualitative approaches were used to analyze the data. All the data collected is based on the Theory of Subtitling Strategies according to Gottlieb (1992) and the Theory of Translation Equivalence according to Nida (1964). The result of the analysis shows that only six of ten subtitling strategies and the analysis shows two combinations of subtitling strategies were applied by the translator in the subtitle translation. Transfer strategy is the most frequently used. The result of the data shows that the translation of Encanto’s movie subtitle is equivalent. It shows that Formal equivalence appears more than Formal equivalence. Another finding in this research is that the translator could use more than two strategies in English movies with Spanish culture.